The old blue pickup truck - Ransom, Candice F., 1952-; Mattheson, Jenny (New York : Walker, 2009)
As a girl and her father run errands in their old blue pickup, she discovers how many different ways they can use their truck.
Kirkus Review.
School Library Journal.
2.6
K-3
Keywords: Fathers and daughters -- Juvenile fiction; Trucks -- Juvenile fiction; Fathers and daughters -- Fiction; Trucks -- Fiction; Father-daughter relationship -- Fiction; Trucks -- Fiction; Picture books for children